Effects of Local Feed Supplementation on the Performance of Bligon Goat Does at the End of Gestation Reared in West Timor Savannah - Manu, AE; Baliarti, E; Keman, S; Datta, FU (ANIMAL PRODUCTION, 2007)
The research was conducted in Lili savanna, West Timor. Â The aims were to study the effects of local feed supplementation on performances of Bligon does at late gestation period reared in West Timor savanna during dry season Fifteen Bligon does at late gestation period were used for ten weeks. Does were randomly divided into 3 groups of treatment, namely R0 = control; R1 = R0 + 1% supplementation; and R2 = R0 + 2% supplementation. Results showed that Â average daily gain, kidâs birth weight, colostrum Ig and body condition scores of group R2 (62.5 g, 2.42 kg, 94.8 mg/ml; 2.36, respectivelly) were significantly higher than group R0 (-7.19 g, 1.73 kg, 43 mg/mlÂ ; 2.36, respectively), but were not significantly different from group R1 (51.79 g, 2.25 kg, 71.2 mg/mlÂ ; 3.24, respectively). Blood components (PVC, leukocyte, erythrocyte, Hb, glucose, protein and urea) at the begining of the experiment were similar among groups, however they were significant different (P<0.01) between R2 and R1, R2 and R0, and R1 and R0. Thedifferences in the number oferythrocyte between R1 and R0 were not significant (P>0.05). In conclusion, the performance and health status of Bligon does at late gestation period reared at West Timor savanna during dry season can be increased by local feed supplementation. (Animal Production 9(1): 1-8 (2007)Â Key Words: performance, gestation does, supplement local feed, savanna, dry season